Development of Management Control System Research: Study on Behavioral Research in Accounting Journal (2006–2018) - SeTin, SeTin; Augustine, Yvonne (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 1 (2020), 2020)
This paper provides a descriptive analysis of management control system (MCS) in BRIA journal from 2006 to 2018. A total of 180 articles were examined, resulting in the identification of 34 articles for further analysis. The analysis led to several findings. 1) Most of the articles use quantitative methods, examine MCS at the managerial level, and emphasize one- or two-dimensional control systems. 2) The dominant topics are strategic performance measurement system, budget, reward compensation system, and performance achievement. 3) The dominant independent variables are incentives, psychological, strategy performance measurement systems, and environmental dynamism. 4) The dominant dependent variables are performance and psychological variables. 5) Environmental dynamism and environmental uncertainty are the external contingencies that affect performance, and the most dominant internal contingency is the variable related to individual factors. 6) Finally, the majority of the article use contingency variables that tend to concentrate on increasing the number of independent rather than dependent variables. Keywords : Management control system, BRIA Journal 2006-2018